Updating the distribution and population status of jaguarundi, puma yagouaroundi (É. Geoffroy, 1803) (Mammalia: Carnivora: Felidae), in the southernmost part of its distribution range - Luengos Vidal, Estela Maris (2017)
We report new occurrence records of Puma yagouaroundi (É. Geoffroy, 1803), a widely distributed but little known Neotropical carnivore, obtained over the last 10 years in Buenos Aires province, central Argentina. The records were collected by camera trapping surveys (n = 384 stations) and 195 interviews with local inhabitants. Our results improve our understanding of this species’ geographic range, especially its southernmost limit, and abundance, and confirm the need for more detailed studies to better assess the conservation status of this species in central Argentina and other parts of its range.